Characterization of Depression Among Patients At Urban Primary Healthcare Centers in Oman. (January 2015) - Al-Salmani, Asthma; Juma, Tahara; Al-Noobi, Arwa; Al-Farsi, Yahya; Jaafar, Najlaa; Al-Mamari, Khalsa; Anwar, Huda; Al-Lawati, Ghada; Klein, Thomas J.; Al-Adawi, Samir
Aim: The aim of this study was to estimate the prevalence and predictors of depression among Oman adult population attending primary healthcare clinics (PHCs) in Muscat Governorate in 2011. Methodology: A cross-sectional study was conducted on 2005 participants attending 27 different PHCs in Muscat Governorate during 2011. A Patient Health Questionnaire (PHQ-9), together with a socio-demographic and relevant clinical data questionnaire was administered. Results: Of the 2005 participants, 61.8% were women and 42.1% were of 25-50 age group. Of the total, 44.4% were employed, of whom 51% were government employees. The prevalence of depression among them was 8.1%. The adjusted odds ratios generated by logistic regression models indicated that depression was significantly associated with age greater than 50 years old (OR = 2.23; 95% CI 1.07, 4.22; P = 0.04), female (OR = 1.34; 95% CI 1.12, 3.82; P = 0.03), married (OR = 1.91; 95% CI 1.11, 3.30; P = 0.02), graduated or attended higher education (OR = 1.40; 95% CI 1.03, 2.66; P = 0.04), working in the private sector if employed (OR = 1.72; 95% CI 1.08, 2.75; P = 0.02), and having chronic illness such as diabetes mellitus, hypertension, asthma, heart, thyroid, and renal diseases (OR = 1.82; 95% CI 1.03, 3.51; P = 0.01). Conclusion: The rate of depression appears to be in the lower range compared to rate reported from elsewhere. Some socio-cultural factors that may contribute to the present findings are discussed.